Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1097/brs.0b013e31821f4a51
|View full text |Cite
|
Sign up to set email alerts
|

Five-year Follow-up Evaluation of Surgical Treatment for Cervical Myelopathy Caused by Ossification of the Posterior Longitudinal Ligament

Abstract: ADF is considered especially suitable for cases with massive OPLL and preoperative kyphotic alignment of the cervical spine, although it leads to a higher incidence of surgery-related complications compared with LAMP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
156
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(162 citation statements)
references
References 22 publications
6
156
0
Order By: Relevance
“…24,31,36,44,48 There were a total of 5 cases of OPLL progression among a total of 1222 patients (0.41%) in the decompression and fusion population and a total of 48 cases of OPLL progression among a total of 745 patients (6.4%) in the posterior decompression-only population.…”
Section: Progression Of Opllmentioning
confidence: 99%
See 4 more Smart Citations
“…24,31,36,44,48 There were a total of 5 cases of OPLL progression among a total of 1222 patients (0.41%) in the decompression and fusion population and a total of 48 cases of OPLL progression among a total of 745 patients (6.4%) in the posterior decompression-only population.…”
Section: Progression Of Opllmentioning
confidence: 99%
“…5,8,10,14,25,27,35,44,46,48,50,52 Some of the most commonly reported complications after cervical decompression and fusion surgery include CSF leaks and pseudarthrosis, whereas posterior decompression is more commonly associated with neurological deterioration, persistent neuropathic pain in the extremities, and progression of kyphotic change. 6,14 Previous studies have demonstrated an increased incidence of complications after decompression and fusion compared with decompression only.…”
Section: Complications and Revision Surgeries In Patients Who Underwementioning
confidence: 99%
See 3 more Smart Citations